Meet a Veterinarian! - Anderson, AnnMarie; Hunt, Lisa (Lisa Jane); 1973- (New York : Childrens Press, an imprint of Scholastic Inc, 2022)
"This book introduces readers to the role of veterinarians in their neighborhood"--
Ages 5-7.
Grades K-1.
Keywords: Veterinarians -- Juvenile literature; Veterinary medicine -- Juvenile literature; Readers (Primary); Nonfiction